Conductive paste based on seed silver powder and preparation method thereof
By using conductive paste based on seed silver powder in photovoltaic cells, the problems of high cost of traditional conductive paste and poor interlayer bonding performance are solved, and more efficient photoelectric conversion efficiency and more stable photovoltaic module performance are achieved.
Patent Information
- Application Number
- CN202411525042.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-30
AI Technical Summary
The traditional seed layer conductive paste has high cost and under large temperature changes, microscopic cracks are prone to occur between the layers, resulting in an increase in the internal resistance of the battery cell, which in turn reduces the photoelectric conversion efficiency.
A conductive paste based on seed silver powder is used, which consists of seed silver powder, glass powder and organic carrier, and a silver-coated base metal-type seed silver powder is formed by a specific preparation method to improve the cost-effectiveness and interlayer bonding performance of the conductive paste.
This conductive paste exhibits high efficiency in the photo-induced plating technology. The contact surface between the sintered layer and the plating layer increases, which reduces the overall resistivity, improves the bonding intensity, alleviates the problem of decreasing photoelectric conversion efficiency, and improves the overall efficiency of photovoltaic modules.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photovoltaic cells, and in particular, relates to a conductive paste based on seed silver powder and a preparation method thereof. Background Art
[0002] Photovoltaic power generation, as a way to directly convert solar energy into electrical energy, has the advantages of being environmentally friendly and renewable, and is one of the important directions for developing green and clean energy. Conductive paste is a key material in the production of photovoltaic cells, mainly used to make the front and back grids of solar cells.
[0003] The traditional grid uses screen printing technology to directly print and sinter the conductive paste into shape. The aspect ratio of the grid is difficult to improve. The seed layer plus light-induced electroplating technology can effectively improve the aspect ratio of the grid, reduce the resistivity of the grid, increase the light-receiving area of the cell, and reduce the amount of grid silver paste, which has a positive significance for reducing the cost of photovoltaic cells and improving the photoelectric conversion efficiency; however, the seed layer conductive paste is mostly based on ultra-fine silver powder, resulting in high cost. In addition, there is a difference in the fineness of the seed layer and the electroplating layer. During long-term use, especially under conditions with large temperature changes, micro cracks are prone to appear between the layers, and accompanied by the electrochemical action of the interlayer current, the interlayer bonding performance is further deteriorated, resulting in an increase in the internal resistance of the cell, thereby reducing the photoelectric conversion efficiency. Therefore, the present application aims to provide a conductive paste for the seed layer. Summary of the invention
[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a conductive paste based on seed silver powder and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A conductive paste based on seed silver powder consists of the following components: 10-85wt% of seed silver powder, 2-5wt% of glass powder and 8-12wt% of organic carrier, and the balance is spherical silver powder.
[0007] The seed silver powder is prepared by the following method:
[0008] Step A1: Mix triallylamine, mercaptoethanol and ethanol, raise the temperature to 55-65°C, apply 120-160rpm stirring to activate for 20-30min, then add photoinitiator and mix with 200-300W / m 2 The reaction was carried out under ultraviolet irradiation for 2.5-3 hours. After the reaction was completed, ethanol was removed by rotary evaporation to obtain an intermediate;
[0009] Furthermore, the dosage ratio of triallylamine, mercaptoethanol, photoinitiator and ethanol is 0.1mol:0.3mol:0.25-0.3mL:3-4mmol:80-100mL, the photoinitiator is preferably liquid photoinitiator 1173, triallylamine and mercaptoethanol are activated by heating, and then click-addition is carried out under photoinitiation to form a central nitrogen-containing thioether compound.
[0010] Step A2: The intermediate, sodium methoxide and tetrahydrofuran are mixed, heated to reflux for 1-1.3 hours, and then trichloroethyl phosphate dispersion and triethylamine are added, the temperature is controlled at 60-70°C, and the reaction is stirred at 60-90 rpm for 5.5-7 hours. After the reaction is completed, low boiling points are removed by rotary evaporation to obtain an adsorbent;
[0011] Furthermore, the dosage ratio of the intermediate, trichloroethyl phosphate, sodium methoxide, triethylamine and tetrahydrofuran is 0.1 mol: 70-85 mmol: 25-30 mmol: 8-12 mL: 55-75 mL, the volume fraction of the trichloroethyl phosphate dispersion is 30-40%, and under the promotion of sodium methoxide and triethylamine, the intermediate and trichloroethyl phosphate are etherified to form a small molecular weight network compound.
[0012] Step A3: premix the base metal powder, the adsorbent, the nonionic surfactant and dimethylacetamide, add the silver nitrate solution and stir for 30-40 minutes, introduce nitrogen protection, slowly add the hydrazine hydrate solution under ultrasonic oscillation and react for 1.5-2 hours, let it stand and settle after the reaction, remove the supernatant and dry to obtain a composite precursor;
[0013] Furthermore, the amount ratio of base metal powder, silver nitrate, hydrazine hydrate solution, attachment agent, non-ionic surfactant and dimethylacetamide is 1g:3.8-14.2g:0.8-1.1mL:0.4-0.6g:0.25-0.3g:35-50mL, the mass fraction of silver nitrate solution is 10%, the volume fraction of hydrazine hydrate solution is 40%, the non-ionic surfactant is preferably Tween 80, the nitrogen-containing sulfide structure in the attachment agent molecule forms a stable strong chelation, and preferentially chelates and combines with the active sites on the surface of the base metal powder, so that the attachment agent is attached to the surface of the base metal powder, while the phosphorus oxygen structure in the attachment agent molecule has a weak chelation effect and is enriched on the surface of the base metal powder to capture silver ions, thereby forming an initial silver ion enrichment layer, and then in the hydrazine hydrate reduction process, elemental silver grows on the surface with the initial complex as the core.
[0014] Furthermore, the base metal powder is one of copper powder, nickel powder and iron powder, and the average particle size is not higher than 1 μm.
[0015] Step A4: The composite precursor is first heated to 550-620°C in a nitrogen atmosphere and calcined for 1.8-2.4h, and then continued to heat to 880-920°C and calcine for 1-1.2h. It is then cooled to room temperature and ground and dispersed to obtain seed silver powder. The organic matter in the composite precursor is thermally decomposed by the additive to form a silver adhesion layer containing a large number of pores on the surface of the base metal powder.
[0016] Preferably, the melting point of the glass powder is 600-700° C. At this melting point, the silver paste is easy to sinter and become dense.
[0017] Preferably, the average particle size of the spherical silver powder should not exceed 5 μm, which is beneficial to improving the flatness of the gate after sintering.
[0018] A method for preparing a conductive paste based on seed silver powder comprises the following specific steps: premixing seed silver powder, glass powder and spherical silver powder, adding an organic carrier, grinding and slurrying, and obtaining the conductive paste.
[0019] Beneficial effects of the present invention:
[0020] The invention discloses a preparation method of silver-coated base metal seed silver powder, which comprises the following steps: light-induced addition reaction of triallylamine and mercaptoethanol to prepare a nitrogen-containing sulfide compound, namely an intermediate, and then, under the promotion of sodium methoxide and triethylamine, the intermediate is subjected to an etherification reaction with trichloroethyl phosphate to prepare a small molecular weight network compound, namely an attached agent, which is then compounded with metal micropowder in a liquid phase environment, and the nitrogen-containing sulfide structure in the attached agent molecule forms a stable strong chelation effect, which preferentially chelates and combines with the active sites on the surface of the base metal micropowder, so that the attached agent is attached to the surface of the base metal micropowder. The phosphorus-oxygen structure in the attached agent molecule has a weak chelating effect, and the silver ions added later are captured to form an initial silver ion enrichment layer on the surface of the base metal micropowder. The elemental silver is grown on the surface through hydrazine hydrate reduction to form a composite precursor. Finally, the organic matter in the composite precursor is thermally decomposed by the attached agent to form a silver attachment layer containing a large number of pores on the surface of the base metal powder. This method has low limitations on the types of base metals, and suitable base metals can be selected as the core according to the application requirements of the conductive paste. The product has high designability and can reduce the application cost of the conductive paste to a large extent. In addition, the introduction of seed silver powder makes the conductive paste more suitable for light-induced electroplating technology. The surface of the seed silver powder contains a large number of silver pores. After sintering, microscopic pores are evenly introduced into the surface of the sintered layer. Local high current density is formed inside these pores during the electroplating process, and silver is preferentially deposited to form "silver pins" interspersed in the sintered layer. On the one hand, the contact surface between the sintered layer and the electroplated layer is improved, which is conducive to reducing the overall resistivity. On the other hand, the bonding strength between the sintered layer and the electroplated layer is increased, which slows down the problem of decreased photoelectric conversion efficiency caused by stratification of the contact interface, and is conducive to improving the overall efficiency of photovoltaic modules during their service life. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1, preparing a conductive paste based on seed silver powder, the specific implementation process is as follows:
[0023] (1) Preparation of seed silver powder
[0024] Step A1: Mix triallylamine, mercaptoethanol and ethanol, heat to 65°C, stir at 160 rpm for 20 min, add photoinitiator and mix with 300 W / m 2 The reaction was carried out under ultraviolet irradiation for 2.5 hours, wherein the dosage ratio of triallylamine, mercaptoethanol, photoinitiator and ethanol was 0.1 mol: 0.3 mol: 0.3 mL: 4 mmol: 100 mL, and the photoinitiator used was commercially available photoinitiator 1173. After the reaction was completed, ethanol was removed by rotary evaporation to obtain an intermediate.
[0025] Step A2: The intermediate, sodium methoxide and tetrahydrofuran are mixed, heated to reflux for 1 hour, and then trichloroethyl phosphate dispersion and triethylamine are added, the temperature is controlled to 70°C, and the reaction is stirred at 90 rpm for 5.5 hours, wherein the amount ratio of the intermediate, trichloroethyl phosphate, sodium methoxide, triethylamine and tetrahydrofuran is 0.1 mol: 85 mmol: 30 mmol: 12 mL: 75 mL, the trichloroethyl phosphate dispersion uses carbon tetrachloride as a dispersion solvent, and the volume fraction of trichloroethyl phosphate is 40%. After the reaction, low-boiling substances including carbon tetrachloride and tetrahydrofuran are removed by rotary evaporation to obtain an adsorbent.
[0026] Step A3: pre-mix base metal powder, an adsorbent, a nonionic surfactant and dimethylacetamide, add silver nitrate solution and stir for 30 minutes, introduce nitrogen protection, apply 20kHz ultrasonic oscillation, slowly add hydrazine hydrate solution and react for 1.5 hours, wherein the base metal powder is selected from Brofos-Fe-800 iron powder with an average particle size of 800nm, the nonionic surfactant is selected from commercially available Tween 80, the silver nitrate solution is an aqueous solution with a mass fraction of 10%, the hydrazine hydrate solution is an industrial raw material with a volume fraction of 40%, the amount ratio of base metal powder, silver nitrate, hydrazine hydrate solution, adsorbent, nonionic surfactant and dimethylacetamide is 1g:3.8g:1.1mL:0.6g:0.3g:50mL, after the reaction is completed, let it stand and precipitate, remove the supernatant and dry to obtain a composite precursor.
[0027] Step A4: Place the composite precursor in a nitrogen atmosphere furnace preheated to 300°C, first heat it to 620°C and bake it for 1.8h, then continue to heat it to 920°C and bake it for 12h, then cool it to room temperature and grind and disperse it to obtain seed silver powder.
[0028] (2) Preparation of conductive paste
[0029] Ingredients: The raw materials are taken according to the weight percentage, 10wt% of seed silver powder, which is homemade in this embodiment; 2wt% of glass powder, GT45 glass powder is used in the implementation process, and the melting point is about 635°C; 8wt% of organic carrier, which is compounded by dibutyl phthalate, ethyl cellulose, xylene and pinene alcohol in a mass ratio of 1:0.15:0.8:0.5 in the implementation process; 80wt% of spherical silver powder, Brofos-Ag-W03 raw material is used in the implementation process.
[0030] Pulping: The seed silver powder, glass powder and spherical silver powder are mixed at a high speed of 1000 rpm in a high-speed mixer for 10 minutes, and then an organic carrier is added to a grinder for cyclic grinding for 15 minutes to obtain a conductive paste.
[0031] Example 2, preparing a conductive paste based on seed silver powder, the specific implementation process is as follows:
[0032] (1) Preparation of seed silver powder
[0033] Step A1: Mix triallylamine, mercaptoethanol and ethanol, heat to 55°C, stir at 120 rpm for 30 min, add photoinitiator and mix with 200 W / m 2 The reaction was carried out under ultraviolet irradiation for 3 hours, wherein the dosage ratio of triallylamine, mercaptoethanol, photoinitiator and ethanol was 0.1 mol: 0.3 mol: 0.25 mL: 3 mmol: 80 mL, and the photoinitiator used was commercially available photoinitiator 1173. After the reaction was completed, ethanol was removed by rotary evaporation to obtain an intermediate.
[0034] Step A2: Take the intermediate, sodium methoxide and tetrahydrofuran, mix them, heat them up and reflux them for 1.3 hours, then add trichloroethyl phosphate dispersion and triethylamine, control the temperature to 60°C, and stir at 60rpm to react for 7 hours, wherein the amount ratio of the intermediate, trichloroethyl phosphate, sodium methoxide, triethylamine and tetrahydrofuran is 0.1 mol: 70 mmol: 25 mmol: 8 mL: 55 mL, the trichloroethyl phosphate dispersion uses carbon tetrachloride as the dispersion solvent, and the volume fraction of trichloroethyl phosphate is 30%. After the reaction, the low-boiling substances including carbon tetrachloride and tetrahydrofuran are removed by rotary evaporation to obtain the adsorbent.
[0035] Step A3: pre-mix base metal powder, an adsorbent, a nonionic surfactant and dimethylacetamide, add silver nitrate solution and stir for 40 minutes, introduce nitrogen protection, apply 25kHz ultrasonic oscillation, slowly add hydrazine hydrate solution and react for 2 hours, wherein the base metal powder is selected from Brofos-Ni-800 nickel powder with an average particle size of 800nm, the nonionic surfactant is selected from commercially available Tween 80, the silver nitrate solution is an aqueous solution with a mass fraction of 10%, the hydrazine hydrate solution is an industrial raw material with a volume fraction of 40%, the amount ratio of base metal powder, silver nitrate, hydrazine hydrate solution, adsorbent, nonionic surfactant and dimethylacetamide is 1g:14.2g:0.8mL:0.4g:0.253g:35mL, after the reaction is completed, the mixture is allowed to stand for precipitation, the supernatant is removed and dried to obtain a composite precursor.
[0036] Step A4: Place the composite precursor in a nitrogen atmosphere furnace preheated to 300°C, first heat it to 550°C and bake it for 2.4h, then continue to heat it to 880°C and bake it for 1.2h, and then cool it to room temperature and grind and disperse it to obtain seed silver powder.
[0037] (2) Preparation of conductive paste
[0038] Ingredients: The raw materials are taken according to the weight percentage, 55wt% of seed silver powder, which is homemade in this embodiment; 4wt% of glass powder, GT45 glass powder is used in the implementation process, and the melting point is about 635°C; 12wt% of organic carrier, which is compounded by dibutyl phthalate, ethyl cellulose, xylene and pinene alcohol in a mass ratio of 1:0.12:1.1:0.4 in the implementation process; 29wt% of spherical silver powder, Brofos-Ag-W03 raw material is used in the implementation process.
[0039] Pulping: The seed silver powder, glass powder and spherical silver powder are mixed at a high speed of 1000 rpm in a high-speed mixer for 10 minutes, and then an organic carrier is added to a grinder for cyclic grinding for 15 minutes to obtain a conductive paste.
[0040] Example 3, preparing a conductive paste based on seed silver powder, the specific implementation process is as follows:
[0041] (1) Preparation of seed silver powder
[0042] Step A1: Mix triallylamine, mercaptoethanol and ethanol, heat to 60°C, stir at 160 rpm for 30 min, add photoinitiator and mix with 240 W / m 2The reaction was carried out under ultraviolet irradiation for 2.8 hours, wherein the dosage ratio of triallylamine, mercaptoethanol, photoinitiator and ethanol was 0.1 mol: 0.3 mol: 0.28 mL: 4 mmol: 90 mL, and the photoinitiator used was commercially available photoinitiator 1173. After the reaction was completed, ethanol was removed by rotary evaporation to obtain an intermediate.
[0043] Step A2: Take the intermediate, sodium methoxide and tetrahydrofuran, mix them, heat them up and reflux them for 1.2 hours, then add trichloroethyl phosphate dispersion and triethylamine, control the temperature to 70°C, and stir at 90rpm to react for 6.5 hours, wherein the amount ratio of the intermediate, trichloroethyl phosphate, sodium methoxide, triethylamine and tetrahydrofuran is 0.1 mol: 75 mmol: 30 mmol: 10 mL: 70 mL, the trichloroethyl phosphate dispersion uses carbon tetrachloride as a dispersion solvent, and the volume fraction of trichloroethyl phosphate is 30%. After the reaction, the low-boiling substances including carbon tetrachloride and tetrahydrofuran are removed by rotary evaporation to obtain an adsorbent.
[0044] Step A3: pre-mix base metal powder, an adsorbent, a nonionic surfactant and dimethylacetamide, add silver nitrate solution and stir for 40 minutes, introduce nitrogen protection, apply 25kHz ultrasonic oscillation, slowly add hydrazine hydrate solution and react for 1.8 hours, wherein the base metal powder is selected from Brofos-Cu-800 copper powder with an average particle size of 800nm, the nonionic surfactant is selected from commercially available Tween 80, the silver nitrate solution is an aqueous solution with a mass fraction of 10%, the hydrazine hydrate solution is an industrial raw material with a volume fraction of 40%, the amount ratio of base metal powder, silver nitrate, hydrazine hydrate solution, adsorbent, nonionic surfactant and dimethylacetamide is 1g:10.5g:0.9mL:0.5g:0.28g:45mL, after the reaction is completed, the mixture is allowed to stand for precipitation, the supernatant is removed and dried to obtain a composite precursor.
[0045] Step A4: Place the composite precursor in a nitrogen atmosphere furnace preheated to 300°C, first heat it to 600°C and bake it for 2.2h, then continue to heat it to 920°C and bake it for 1h, then cool it to room temperature and grind and disperse it to obtain seed silver powder.
[0046] (2) Preparation of conductive paste
[0047] Ingredients: raw materials are taken according to weight percentage, seed silver powder 85wt%, which is self-made in this embodiment; glass powder 5wt%, FD66A type glass powder is used in the implementation process, and the melting point is about 700℃; organic carrier 10wt%, dibutyl phthalate, ethyl cellulose, xylene and terpineol are compounded in a mass ratio of 1:0.12:1:0.5 in the implementation process.
[0048] Pulping: The seed silver powder and the glass powder are mixed at a high speed of 1000 rpm in a high-speed mixer for 10 minutes, and then an organic carrier is added to a grinder for cyclic grinding for 15 minutes, and the conductive slurry is obtained.
[0049] Comparative Example 1
[0050] This comparative example refers to Example 3, except that the seed silver powder is replaced with spherical silver powder, and the rest of the implementation process is exactly the same.
[0051] Comparative Example 2
[0052] This comparative example refers to Example 3, except that the seed silver powder is replaced with silver-coated copper powder of the same weight ratio, selected from Brofos-CuAg30-W02 type raw material, and the rest of the implementation process is exactly the same.
[0053] A 156×156 mm silicon wafer was used as the substrate, and the conductive paste prepared as above was printed on the surface, sintered and photoinduced silver plating was performed to obtain a battery silicon wafer. The initial resistivity ρ0 was detected using a SZT-B four-probe tester. The battery silicon wafer was placed in a variable temperature box and cycled at 0-70°C to simulate the actual working temperature. The single cycle time was 2 hours, and the test cycle was 1000 hours. After that, the temperature-dependent resistivity ρ1 was tested. The initial conversion efficiency Eff0 and the temperature-dependent conversion efficiency Eff1 were tested using a Berger tester. The specific test results are shown in Table 1:
[0054] Table 1
[0055]
[0056] It can be seen from the test results in Table 1 that the initial resistivity of the cell silicon wafer prepared by the conductive paste of the embodiment is slightly higher than that of the comparative example 1, and the initial conversion efficiency is slightly lower than that of the comparative example 1. However, compared with the comparative example 2, the initial resistivity is significantly reduced, and the photoelectric conversion efficiency is significantly improved. Moreover, the decrease in the photoelectric conversion efficiency after the temperature change cycle test is even lower, which is beneficial to maintaining the stability of the photovoltaic cell.
[0057] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0058] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A conductive paste based on seed silver powder, characterized in that: The method comprises the following components: 10-85wt% of seed silver powder, 2-5wt% of glass powder and 8-12wt% of organic carrier, and the balance is spherical silver powder; The seed silver powder is prepared by the following method: Step A1: Mix triallylamine, mercaptoethanol and ethanol, heat to 55-65°C, stir and activate for 20-30 minutes, then add photoinitiator and mix with 200-300W / m 2 The reaction was carried out under ultraviolet irradiation for 2.5-3 hours. After the reaction was completed, the ethanol was removed by rotary evaporation to obtain an intermediate; Step A2: The intermediate, sodium methoxide and tetrahydrofuran are mixed, heated to reflux for 1-1.3 hours, and then trichloroethyl phosphate dispersion and triethylamine are added, and the temperature is controlled at 60-70° C. and stirred for reaction for 5.5-7 hours. After the reaction is completed, low-boiling substances are removed by rotary evaporation to obtain an adsorbent; Step A3: premix the base metal powder, the adsorbent, the nonionic surfactant and dimethylacetamide, add the silver nitrate solution and stir for 30-40 minutes, introduce nitrogen protection, slowly add the hydrazine hydrate solution under ultrasonic oscillation and react for 1.5-2 hours, let it stand and settle after the reaction, remove the supernatant and dry to obtain a composite precursor; Step A4: The composite precursor is first heated to 550-620°C in a nitrogen atmosphere and calcined for 1.8-2.4h, and then continued to be heated to 880-920°C and calcined for 1-1.2h. It is then cooled to room temperature and ground and dispersed to obtain seed silver powder.
2. The conductive paste based on seed silver powder according to claim 1, characterized in that: The usage ratio of the intermediate, trichloroethyl phosphate, sodium methoxide, triethylamine and tetrahydrofuran is 0.1 mol: 70-85 mmol: 25-30 mmol: 8-12 mL: 55-75 mL.
3. The conductive paste based on seed silver powder according to claim 2, characterized in that: The dosage ratio of base metal powder, silver nitrate, hydrazine hydrate solution, adsorbent, non-ionic surfactant and dimethylacetamide is 1g: 3.8-14.2g: 0.8-1.1mL: 0.4-0.6g: 0.25-0.3g: 35-50mL, and the volume fraction of hydrazine hydrate solution is 40%.
4. The conductive paste based on seed silver powder according to claim 3, characterized in that: The base metal powder is one of copper powder, nickel powder and iron powder, and the average particle size is not higher than 1 μm.
5. The conductive paste based on seed silver powder according to claim 1, characterized in that: The melting point of glass powder is 600-700℃.
6. The conductive paste based on seed silver powder according to claim 1, characterized in that: The average particle size of the spherical silver powder does not exceed 5 μm.
7. A method for preparing a conductive paste based on seed silver powder according to any one of claims 1 to 6, characterized in that: The specific method is: premixing seed silver powder, glass powder and spherical silver powder, then adding an organic carrier to grind and slurry to obtain a conductive slurry.
Citation Information
Patent Citations
Light-facing side seed layer silver paste of crystalline silicon solar cell, preparation method of light-facing side seed layer silver paste, crystalline silicon solar cell, and preparation method of crystalline silicon solar cell
CN104078091A
Silver-coated copper powder slurry capable of being sintered in air and preparation method thereof
CN110211724A